The epistemic and ethical onus of 'One Health'. (20th October 2018) - Beever, Jonathan; Morar, Nicolae
Abstract: This paper argues that the practical reach and ethical impact of the One Health paradigm is conditional on satisfactorily distinguishing between interconnected and interdependent factors among human, non‐human, and environmental health. Interconnection does not entail interdependence. Offering examples of interconnections and interdependence in the context of existing One Health literature, we demonstrate that the conversations about One Health do not yet sufficiently differentiate between those concepts. They tend to either ignore such distinctions or embrace bioethically untenable positions. We conclude that careful conceptual differentiation can prevent One Health stakeholders either from over‐reaching or under‐reaching the practical and ethical boundaries of this developing paradigm.